EVALUATION OF POLLUTION OF DIYALA RIVER WATER QUALITY BY SOME HEAVY METALS (PB, CU, NI, CD) , BORON AND THEIR EFFECT ON POLLUTION OF AGRICULTURAL SOILS - Kadhim Makki Naser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A study was conducted to evaluate the quality of Diyala River water with some heavy metals (Pb, Cu, Ni, Cd), Boron and their effect on pollution of agricultural soil surrounding river that is irrigated with river water. Nine areas located on river within Al-Jisr district of Al-Madain district, southeast of Baghdad Governorate / Iraq, were selected, namely Umm Al-Ubaid, Al-Uwaija, Al-Khafaji, Al-Kargouliya, Jurf Al-Naddaf, Al-Samadiyah, Abu Thila, Al-Arifiyah, Al-Tuwaitha, and northern shores of Salman Pak, for comparison purposes. Water samples were taken for three months during summer (June, July, and August) and three months during the winter (January, February, and March) of 2024, and average values ​​for two seasons were taken. Soil samples were collected from agricultural soils adjacent to the river in above-mentioned areas at same time that water samples were taken. Results indicated a difference in chemical properties of studied water and soil during two seasons, as highest values ​​for electrical conductivity, soil reaction, cataions and anaions dissolved, heavy metals ions and boron were in summer season compared to winter season in all sites, highest values ​​were in Tuwaitha region. Water category was most dangerous in Al-Tuwaitha area C3S1 low-sodium high-salinity according to USDA system, while its classification was a severe problem and an increasing problem for two areas above, according to FAO system. Concentrations of Lead, Cadmium, Nickel and Copper exceeded permissible limits for irrigation water in both seasons for all sites except northern Salman Pak beaches (comparison). All agricultural soils are contaminated with Cadmium, not contaminated with Lead and Copper.